Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevfluids.3.124307
|View full text |Cite
|
Sign up to set email alerts
|

Drying and percolation in correlated porous media

Abstract: We study how the dynamics of a drying front propagating through a porous medium are affected by small-scale correlations in material properties. For this, we first present drying experiments in micro-fluidic micro-models of porous media. Here, the fluid pressures develop more intermittent dynamics as local correlations are added to the structure of the pore spaces. We also consider this problem numerically, using a model of invasion percolation with trapping, and find that there is a crossover in invasion beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
6
15
0
Order By: Relevance
“…In both cases, the power law exponent does not change as the fracture aperture changes from first contact case to the highly stressed case. Our expectation for = 2 exponent is due to (1) the theoretical results for SOC processes (Maslov, 1995), (2) the fact that a similar exponent is observed for porous media displacements (Aker et al, 2000;Biswas et al, 2018;Furuberg et al, 1996), and most importantly (3) the fact that this is the exponent observed for purely random fractures with no spatial correlation in the fracture gap ( Figure 2). The fact that the distribution of avalanche sizes for IP without in-plane curvature deviates from the theoretical power law with exponent = 2 (Figure 3c) suggests that it lacks the necessary physics to properly model the invasion process through a self-affine rough fracture.…”
Section: 1029/2019gl082744mentioning
confidence: 55%
See 4 more Smart Citations
“…In both cases, the power law exponent does not change as the fracture aperture changes from first contact case to the highly stressed case. Our expectation for = 2 exponent is due to (1) the theoretical results for SOC processes (Maslov, 1995), (2) the fact that a similar exponent is observed for porous media displacements (Aker et al, 2000;Biswas et al, 2018;Furuberg et al, 1996), and most importantly (3) the fact that this is the exponent observed for purely random fractures with no spatial correlation in the fracture gap ( Figure 2). The fact that the distribution of avalanche sizes for IP without in-plane curvature deviates from the theoretical power law with exponent = 2 (Figure 3c) suggests that it lacks the necessary physics to properly model the invasion process through a self-affine rough fracture.…”
Section: 1029/2019gl082744mentioning
confidence: 55%
“…Measurements of P c during slow drainage through porous media are reported routinely (Biswas et al, 2018;Furuberg et al, 1996;Måløy et al, 1992;Moebius & Or, 2014;Moura et al, 2015Moura et al, , 2017Ramstad & Hansen, 2006). However, to the best of our knowledge, P c measurements during slow drainage through a rough fracture, for a flow rate controlled boundary condition, have only been reported in the pioneer experimental work of Persoff and Pruess (1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations